2021
DOI: 10.15376/biores.16.4.6891-6909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dowels on the mechanical properties of wooden composite beams in ancient timber structures

Abstract: In order to provide more accurate suggestions for the restoration of ancient timber buildings, five types of specimens were designed for static loading tests. The tree species used for the specimens was larch. The wooden composite beams were composed of purlins, tie plates, and fangs. The study analyzed the effects of the number and position of dowels on the mechanical behaviors of wooden composite beams in ancient timber buildings. The bending moment, slippage, strain of the wooden composite beams under the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The quasi-static test of wooden column was conducted at the Engineering Structure Experiment Center of the Beijing University of Technology (Beijing, China). [13] The loading method of this test was selected according to JGJ/T 101 (2015) [14]. Cyclic loading was controlled by displacement.…”
Section: Methodsmentioning
confidence: 99%
“…The quasi-static test of wooden column was conducted at the Engineering Structure Experiment Center of the Beijing University of Technology (Beijing, China). [13] The loading method of this test was selected according to JGJ/T 101 (2015) [14]. Cyclic loading was controlled by displacement.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the tensile performance of mortise and tenon joints was the worst when considering the interaction of four different factors. Han [15] et al designed ve types of larch wood composite beam specimens for static load experiments to investigate the effects of the number and location of tenons on the mechanical properties of wood structural stacked beams. The results showed that tenons can improve the exural load capacity of wooden composite beams, and uniform distribution reduces the sliding effect.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2020) established a stacked beam containing Pupai fang using the Yingxian wooden pagoda of the Liao dynasty as a reference prototype, and obtained parameters such as hysteresis curves by means of a proposed static lateral resistance test method and proposed a simplified load-displacement model with three-line segments. Han et al (2021) investigated the effect of the number and position of nails on the bending moment, slip, deflection, and ultimate load carrying capacity of Qing dynasty stacked purlins by means of a three-point bending test method. Sun et al (2020) used a stacked purlin in a Qing dynasty ridge part as a model and measured the moment-angle hysteresis curve through a proposed static test to analyse the force-deformation characteristics and damage modes of the node.…”
Section: Introductionmentioning
confidence: 99%